Secret files of the Inquisition. - Rabinovitch, John David; Feore, Colm, 1958- (Inquisition Productions, Inc., 2005)
In the 12th century, an upstart Christian sect called Catharism challenges Church doctrine and the absolute power of the Pope. Pope Innocent III declares a Holy War to kill these people. The remote French village of Montaillou is the last stronghold of the Cathars. One man, Bishop Jacques Fournier, becomes one of the most skilled interrogators of the Holy Inquisition.